An algorithm to assign storage areas of products for minimizing mean flow time of pick up trucks - Pathumnakul, Ph.D., Supachai; chaibenjapol, Mr.Nattapol; Arbsuwan, Mr.Withoon; Suwanapichon, Miss Wipada (Engineering and Applied Science Research, 2013)
In this paper, the problem of minimizing mean flow time of pick up trucks is addressed. There is a set of trucks that queue in front of the loading dock of a warehouse waiting to load products. The products are stored in the loading area which is separated into a set of storage areas. All storage areas have equal space. Each storage area contains only a product. A material handling equipment (Forklift) is used to carry product from its storage place to the pick up truck. The objective of this paper is to assign the storage area of each product that minimizes the mean flow time of trucks. In this paper , the mathematical model is formulated and an algorithm is developed to solve some example problems. The results show that the developed algorithm gives solutions that close to the optimal solutions from mathematical model.